Some Predictors of Perceived Support and Proximity in Students during COVID-19 Distance Learning - Pečjak, Sonja; Pirc, Tina; Podlesek, Anja; Peklaj, Cirila (International Electronic Journal of Elementary Education, 2021)
Due to the COVID-19 pandemic, distance learning and social isolation have dramatically changed the social and learning experiences of adolescents. Given that social isolation can adversely affect students’ psychosocial well-being, our study examined the extent to which ICT competences, resilience, and individual types of contact with teachers and classmates contribute to the psychosocial well-being of lower secondary school students (N = 1,813) over an extended period of distance learning. The questionnaires were conducted in groups via videoconferences using the 1ka application. The structural model showed that perceived proximity and support from teachers and classmates as indicators of psychosocial well-being were most strongly predicted by student resilience, teacher organization of group work, student contact with class teachers outside of regular school hours, and contact with classmates through online social networks. These findings have practical applications for teacher education and implementation in teacher practice.